Host-Induced Silencing of FMRFamide-Like Peptide Genes, flp-1 and flp-12, in Rice Impairs Reproductive Fitness of the Root-Knot Nematode Meloidogyne graminicola - Hada, Alkesh; Kumari, Chanchal; Phani, Victor; Singh, Divya; Chinnusamy, Viswanathan; Rao, Uma (Frontiers in Plant Science, 2020)
Rice (Oryza sativa L.) is one of the major staple food crops of the world. The productivity of rice is considerably affected by the root-knot nematode, Meloidogyne graminicola. Modern nematode management strategies targeting the physiological processes have established the potency of use of neuromotor genes for their management. Here, we explored the utility of two FMRFamide like peptide coding genes, Mg-flp-1 and Mg-flp-12 of M. graminicola for its management through host-induced gene silencing (HIGS) using Agrobacterium-mediated transformation of rice. The presence and integration of hairpin RNA (hpRNA) constructs in transgenic lines were confirmed by PCR, qRT-PCR, and Southern and Northern hybridization. Transgenic plants were evaluated against M. graminicola, where phenotypic effect of HIGS was pronounced with reduction in galling by 20–48% in the transgenic plants. This also led to significant decrease in total number of endoparasites by 31–50% for Mg-flp-1 and 34–51% for Mg-flp-12 transgenics. Likewise, number of egg masses per plant and eggs per egg mass also declined significantly in the transgenics, ultimately affecting the multiplication factor, when compared to the wild type plants. This study establishes the effectiveness of the two M. graminicola flp genes for its management and also for gene pyramiding.